(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article analyzes the foundations and importance of the law of obligation in the legislation of Uzbekistan from a scientific and practical point of view. In addition, the importance of obligations in civil-legal relations was analyzed, and suggestions and comments aimed at eliminating problems and shortcomings related to the field were put forward.